Nanoparticle technology handbook - Hosokawa, Masuo; Nogi, Kiyoshi; Naito, Makio; Yokoyama, Toyokazu (Elsevier, 2012)
The updated and expanded second edition of the Nanoparticle Technology Handbook is an authoritative reference providing both the theory behind nanoparticles and the practical applications of nanotechnology. The second edition is thoroughly updated and expanded with sixteen new chapters, providing a reference much broader in scope than the previous edition. Over 140 experts in nanotechnology and/or particle technology contributed to this new edition. Nanoparticle technology is a new and revolutionary technology, which is increasingly being used in electronic devices and nanomaterials. It handles the preparation, processing, application and characterisation of nanoparticles and has become the core of nanotechnology as an extension of the conventional fine particle / powder technology. Nanoparticle technology plays an important role in the implementation of nanotechnology in many engineering and industrial fields including electronic devices, advanced ceramics, new batteries, engineered catalysts, functional paint and ink, drug delivery system, biotechnology, etc.; and makes use of the unique properties of the nanoparticles which are completely different from those of bulk materials. The book includes not only the theory behind nanoparticles, but also the practical applications of nanotechnology. It examines future possibilities and new innovations and contains important knowledge on nanoparticle characterization and the effect of nanoparticles on the environment and on humans. The second edition of Nanoparticle Technology Handbook remains a valuable reference source for scientists and engineers working directly with fine particles and materials or in industries that handle these nanoparticles. Related areas include pharmaceutical products, ink or paint materials, electromagnetic memory devices, ceramic materials and plastic materials with high electro-conductivity. Introduction of all aspects of nanoparticle technology, from the fundamentals to applications Basic information on the preparation through to the characterization of nanoparticles from various viewpoints Information on nanostructures, which play an important role in practical applications Sixty applications of nanoparticles in diverse fields, from which sixteen newly added Up-to-date information given by specialists in each field Information on nanostructures made by nanoparticles, which play a major role in practical applications.